2017
DOI: 10.1016/j.yebeh.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Individual and family factors associated with self-esteem in young people with epilepsy: A multiple mediation analysis

Abstract: . Individual and family factors associated with self-esteem in young people with epilepsy: A multiple mediation analysis. Epilepsy and Behavior, 66, 19-26. DOI: 10.1016/j.yebeh.2016.09.039 Peer reviewed version Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via Elsevier at http://www.sciencedirect.com/science/article/pii/S1525505016303407. Please refer to any applicable ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…For example, one participant shared their unpleasant experience seeking a job after disclosing their disease. Consistent with this study, a previous study reported that negative illness perception negatively affected self-esteem in adolescents with epilepsy (Chew, Haase, & Carpenter, 2017). The school experience can provide chronically ill children with opportunities for successes and failures that can contribute to self-esteem as well as opportunities for developing peer relationships and the ability to learn and cope effectively (Vitulano, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…For example, one participant shared their unpleasant experience seeking a job after disclosing their disease. Consistent with this study, a previous study reported that negative illness perception negatively affected self-esteem in adolescents with epilepsy (Chew, Haase, & Carpenter, 2017). The school experience can provide chronically ill children with opportunities for successes and failures that can contribute to self-esteem as well as opportunities for developing peer relationships and the ability to learn and cope effectively (Vitulano, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…From this research, skewness ranges between À0.361 and À0.831, whereas the kurtosis level ranges between À0.052 and 2.952 (Xiong et al, 2015). It is worth noting that in this study sample, it fell within the acceptable parameters (not > 3.29) for the sample size on the study variables that are part of this research (Tabachnick and Fidell, 2007;Chew et al, 2017).…”
Section: Resultsmentioning
confidence: 61%
“…Räty et al [30] found that illness severity condition was significantly related to the participants' general self-concept but more research is needed to understand the causality of the relationship. Chew et al [31] in a study with adolescents with epilepsy found that illness severity was negatively associated with young people's self-esteem and suggest that young people might have had existing negative views of themselves prior to their illness, and on this basis conclude that self-esteem does not vary as function of illness severity.…”
Section: Discussionmentioning
confidence: 98%